Classification Levels, Approaches, Tools, Application and Challenges in Sentimental Analysis- A Survey - Bharathi, S. Thulasi; Charles, S (International Journal of Computer Sciences and Engineering, 2025)
Sentiment analysis is an application of natural language processing. It is also known as emotion extraction or opinion mining. Sentiment analysis or opinion mining is the computational study of opinions, sentiments and emotions. Opinions are usually particular expressions that designate people’s sentiments, judgments’ or approach toward entities, events and their properties. In general, opinions can be expressed on anything, e.g., a product, a service, an individual, an organization, an event, or a topic. In this paper, the SA classification levels, approaches are discussed. It also reports about various categories of tools used to process the sentimental analysis data. And various application and challenges in sentimental analysis are explained